2019
DOI: 10.1111/jfs.12693
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial mechanism of Tetrapleura tetraptera extract against Escherichia coli and Staphylococcus aureus and its application in pork

Abstract: The antibacterial activity and the mechanism of Tetrapleura tetraptera root extract against Escherichia coli and Staphylococcus aureus were investigated. The mechanism of action of T. tetraptera on tested bacterial species was predominantly characterized by the study of transmission electron microscopy, which revealed severe damage on the primary target which affected the cell integrity and cell membrane permeability. The loss of soluble proteins studied by bacterial protein sodium dodecyl sulfate–polyacrylami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Food‐borne pathogens are major contributors to cause food‐borne diseases. Escherichia coli , Staphylococcus aureus , Salmonella , and so on are all food‐borne pathogens 8 . Infection with E. coli can cause diarrhea, and even may cause symptoms such as hemolytic uremic syndrome and acute renal failure 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food‐borne pathogens are major contributors to cause food‐borne diseases. Escherichia coli , Staphylococcus aureus , Salmonella , and so on are all food‐borne pathogens 8 . Infection with E. coli can cause diarrhea, and even may cause symptoms such as hemolytic uremic syndrome and acute renal failure 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli, Staphylococcus aureus, Salmonella, and so on are all food-borne pathogens. 8 Infection with E. coli can cause diarrhea, and even may cause symptoms such as hemolytic uremic syndrome and acute renal failure. 9 S. aureus can grow in different conditions and it can cause food poisoning when we are infected.…”
Section: Introductionmentioning
confidence: 99%
“…Probably, the presence of linalool might account for the plant’s peppery nature, whereas both γ-terpinene and α-thujene might account for the flavor/fragrance. Elsewhere, the root and stem ethanol extract of T. tetraptera spice respectively obtained 70.14% 25 and 32.01% 10 . Polyphenols like eugenol, quercetin, rutin, and tyrosol, according to Moukette et al .…”
Section: Resultsmentioning
confidence: 99%
“…Acetone Ethanol E.coli 8.00 ± 1.00a 9.33 ± 0.58a 13.00 ± 1.00a Pseudomonas species 8.00 ± 1.00a 9.00 ± 1.00a 11.33 ± 0.58a Staphylococcus aureus 8.67 ± 1.53a 11.67 ± 1.53a 13.33 ± 0.58a Proteus species 9.00 ± 1.00a 10.00 ± 1.00a 12.00 ± 1.73a and absence of tannins and saponin in aqueous and ethanolic extracts of Tetrapleura tetraptera. Also, Lin, et al [29] studied the mechanism of Tetrapleura tetraptera root extract against Escherichia coli and Staphylococcus aureus and reported that plant can disrupt the respiratory metabolism by inhibiting the organism through the Embden-Meyerhof-Parnas and the hexose monophosphate pathways. The authors concluded that plant is effective against antibiotic-resistant strains of pathogens.…”
Section: Isolates Extracts Aqueousmentioning
confidence: 99%